The Effect of Good Corporate Governance (GCG) on The Value of The Company in Manufacturing Companies Listed on The Indonesia Stock Exchange in 2018-2020 - Widyarti, Endang Tri; Suhardjo, Yohanes (Universitas Negeri Semarang, 2021)
All information in the company's financial statements is useful to investors and users of financial statements because the information contained in the financial statements can be taken into account by stakeholders and users of financial statements when making economic decisions. The focus was on attracting the attention of the financial statements and focused only on information about income. The purpose of this study is to find out. Impact of Audit Committee on Good Corporate Governance, Management Ownership and Institutional Ownership on the Enterprise Value of Manufacturing Companies Listed on the Indonesian Stock Exchange in 2018-2020. The population of this study included 75 manufacturing companies. The variables of this study were management ownership, institutional ownership, and corporate value audit committee. Methods of data analysis using multiple linear regression, coefficients of determination, and hypothesis testing. As a result of this study, the management equity regression coefficient was 0.304, t count(3.847) > t table(1.66) and sign(0.000), <(0.04), institution ownership is 0,378, t count (3,678) > t table (1.66) and sign (0.02) < (0.05) and audit committee 0,365, t number (4,387) > t table (1.66) and sign (0.000) <(0.01) based on the coefficient test results R2 determination of 70,4 This refers to institutional assets and administrative ownership of the Audit Committee. Together they have a positive and significant impact on company values. This can be demonstrated in the F test 37,451 of a manufacturing company listed on the Indonesian Stock Exchange in 2018-2020